Sales or Plans: A Comparative Account of the “New” Corporate Reorganization - Ben-Ishai, Stephanie; Lubben, Stephen (McGill Law Journal / Revue de droit de McGill, 2011)
In this article, Professors Stephanie Ben-Ishai and Stephen Lubben explore the recent surge in popularity of “quick sales”, essentially the prereorganization sale of an insolvent debtor’s assets. In their examination of quick sales, the authors use the recent examples of the General Motors, Chrysler, and Lehman Brothers insolvencies to illustrate the popularity and relevance of preplan sales. The authors then move on to a more detailed discussion of the quick-sales process in the United States and Canada, explaining the differences and similarities between both countries’ regimes, and weighing the costs and benefits of each approach. Ultimately, the authors argue that elements of speed and certainty mark the biggest difference between the two jurisdictions, as the American approach offers greater flexibility, which is apt to facilitate quicker asset sales. However, Ben-Ishai and Lubben assert that the Canadian approach also provides significant benefits, particularly in the realm of employee protection and the ability of the monitor to act as an independent check on quick-sales proceedings. Accordingly, the authors conclude that while the American approach is advantageous in situations with exceptional time constraints, the Canadian approach under the Companies Creditors’ Arrangement Act (CCAA) is more beneficial for a typical corporate reorganization, insofar as the role of the monitor and other limitations of the CCAA prevent overuse of the quick-sales process.